Pengaruh Current Ratio, Return on Asset, dan Net Profit Margin terhadap Debt to Equity Ratio pada PT Unilever Indonesia Tbk Periode 2015-2024 - Lestari, Putu Ita; Yasa, I Komang Widya Purnama (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study analyzes the role of liquidity and profitability in determining the capital structure of PT Unilever Indonesia Tbk during the 2015–2024 period. The study uses 40 quarterly data observations sourced from public financial statements and analyzed using multiple linear regression to test the effects of the Current Ratio (CR), Return on Assets (ROA), and Net Profit Margin (NPM) on the Debt-to-Equity Ratio (DER). The results indicate that CR has a negative and significant effect on DER, suggesting that strong liquidity reduces the company’s reliance on debt-based financing. NPM also has a significant negative effect on DER, underscoring the importance of operational profit efficiency in strengthening internal funding. Conversely, ROA does not show a significant effect on DER, indicating that asset-based profitability is not always a determinant of leverage policy. Simultaneously, CR, ROA, and NPM account for most of the variation in DER. This finding makes a theoretical contribution to the study of capital structure by confirming that liquidity and operating profitability are more decisive determinants of leverage than asset efficiency, particularly in mature consumer goods companies that have experienced extreme leverage trends in recent years.